Duração e eficácia do efeito de diferentes anestésicos no bloqueio do nervo digital palmar em equinos - Silva, Gabriele Biavaschi da (2015)
The objective of the present study was to determine the duration and efficacy of local analgesia produced by bupivacaine, lidocaine and ropivacaine used to block the palmar digital (PD) nerve. Nine adult horses underwent a thorough physical examination and evaluation using wireless motion sensors to determine the absence of signs of lameness. Galvanized steel clamps were used to induce lameness. The horses were randomly allocated in a crossover design (bupivacaine 7,5 mg/ml, lidocaine 30 mg, ropivacaine 11,25 mg). The objective lameness evaluations were recorded immediately before administration of the anesthetic on the digital palmar nerve, and then at 5, 10, 15, 30, 60, 90,120, 150, 180, 210, 240 and 300 minutes after the block. The evaluation of mean improvement in lameness after the block was performed using the Wilcoxon test (P> 0.05). The relative lameness severity (RLS) observed after the induction of lameness was 2,4 times the threshold (6mm) and the intensity of the induced lameness was similar between horses (coefficient of variance = 55,26%). Bupivacaine, lidocaine and ropivacaine were effective in blocking at least 75% of the lameness induced by clamps, 5 minutes after the block, the tested drugs improved more than 60% of the lameness. With 7.5 mg bupivacaine improved lameness in more than 90% between 10 and 60 minutes after blocking. Lidocaine (30 mg), resulted in maximal analgesia between 10 and 30 minutes after blocking and the lameness improvement was higher than 69%. Administration of 11.25 mg ropivacaine was able to improve lameness more than 86% between 10 and 180 minutes. The doses of bupivacaine and ropivacaine used in this study were effective in blocking lameness induced by clamps. The dose of 30 mg of lidocaine was not able to completely reverse the lameness. At 5 minutes of blocking, the local anesthetics tested had produced a significant improvement in lameness. Objective analysis of lameness showed a longer analgesic effect on the PD nerve block using ropivacaine than bupivacaine and lidocaine.